Early recurrence after surgery in FIGO 2023 stage I-III endometrial cancer: characteristics and risk factors - Huang, Zhen; Li, Xue; Li, Ling (Frontiers in Oncology, 2025)
BackgroundUnderstanding the risk factors for early recurrence is crucial for improving endometrial cancer (EC) patient outcomes.MethodsWe conducted a retrospective analysis of clinicopathological data from 473 patients diagnosed with EC at the First Affiliated Hospital of Chongqing Medical University between October 2013 and May 2019. We evaluated factors influencing early recurrence(defined as occurring within 12 months after treatment) based on 2023 International Federation of Gynecology and Obstetrics (FIGO) staging system.ResultsAmong the 473 patients, 284 (60.1%) were diagnosed with stage I, 117 (24.7%) with stage II, and 72 (15.2%) with stage III. A total of 343 patients (72.5%) had non-aggressive EC, while 130 patients (27.5%) had aggressive EC. Our findings identified higher FIGO stage, lymphovascular space invasion, estrogen receptor negativity, and abnormal P53 expression as significant independent risk factors for early recurrence. Of the 473 patients, 83 (17.6%) experienced recurrence, with 44 patients (53.0%) relapsing within 12 months post-treatment. Patients with early recurrence had significantly worse prognoses compared to those with late recurrence or no recurrence(P < 0.001).ConclusionThe identification of these risk factors is essential for developing individualized treatment plans and postoperative management strategies. Our study highlights the need for targeted therapies and intensified follow-up for high-risk patients to improve outcomes in endometrial cancer.